Migration in the 21st Century : Political Economy and Ethnography - Gardiner Barber, Pauline; Lem, Winnie (Routledge Advances in Sociology, 2012)
Migration, Political Economy and Ethnography / Pauline Gardiner Barber and Winnie Lem (p.1-13) -- Panoptics of Political Economy: Anthropology and Migration / Winnie Lem (p.17-37) -- Migration and Development Without Methodological Nationalism: Towards Global Perspectives on Migration / Nina Glick Schiller (p.38-63) -- Theorizing Transnational Movement in the Current Conjuncture: Examples from/of/in the Asia Pacific / Donald M. Nonini (p.64-86) -- With Crossings In My Mind: Trinidad's Multiple Migration Flows, Policy and Agency / Belinda Leach (p.89-108) -- Selecting, Competing, and Performing as ‘Ideal Migrants’: Mexican and Jamaican Farmworkers in Canada / Janet McLaughlin (p.109-131) -- In Search of Hope: Mobility and Citizenships on the Canadian Frontier / Lindsay Bell (p.132-152) -- Constructing a "Perfect" Wall: Race, Class, and Citizenship in U.S.–Mexico Border Policing / Josiah McC. Heyman (p.153-174) -- The Aftermath of a Rape Case: The Politics of Migrants´ Unequal Incorporation in Neo-Liberal Times / Bela Feldman-Bianco (p.175-195) -- Gender, Migration and Rural-Urban Relations in Postsocialist China / Yan Hairong (p.196-214) -- "Value Plus Plus": Housewifization and History in Philippine Care Migration / Pauline Gardiner Barber and Catherine Bryan (p.215-235) -- Migration, Political Economy and Beyond / Pauline Gardiner Barber and Winnie Lem (p.236-241)